Pesantren dan Kewirausahaan di Era Kompetisi - Hasbi Indra (Pusat Penerbitan Universitas (P2U) Unisba, 2016)
Abstract: the research of side of qualitative methodes are based of islamic scholars by book or journals for Islamic boarding schools (pesantren) one of a pillar institution deal with to intelligent students for development of nations in the future. In the future, islamic boarding school are face the complicated problems. Pesantren now be a part of national systems and are hoped to reach national level and even international level quality. This time national education have under position in Asian State that are Singapore, Thailand. Malaysia, Philiphine and Vietnam. It looks are not correlated problems with pesantren but the instutituon are a part of national education systems therefore the institution must ready its. In that conditions pesantren are face of globalization fenomenon that are bear result development of science and give easy for humans life and also that contains negative effects such as break of values of human and then the norms of religion had stay. The development of economyc effor in the future in the world are interesting part for well of nation so dealt with a side in free trade amongt of Asian nation. In this era pesantren as institutional education are a parts its could attention for it. Pesantren in the future could attention for horizon santri dealt with very intresting for human life specially about economic in wich give justice deploy it and etics for them in order to create of well of humanity and also give attention to readiness santri with souls entrepreneurship and skill for their life and then could competete by human being in this worlds.Keywords: Islamic boarding school, economic, entrepreneurship